Down stair walking: A simple method to increase muscle mass and performance in 65+ year healthy people. Issue 2 (1st February 2022) - Regnersgaard, Signe; Knudsen, Anna K.; Lindskov, Filippa O.; Mratinkovic, Marija; Pressel, Eckart; Ingersen, Arthur; Dela, Flemming
Abstract: Exercise is important for prevention of sarcopenia in the elderly population. We tested two training modalities, ascending or descending stair walking, representing concentric (CON) and eccentric (ECC) exercise, respectively. We also tested the effects of additional weight during eccentric exercise (ECC+). Thirty-two healthy men and women (70 ± 3 [mean ± SE] yrs.) were randomly assigned to CON, ECC, or ECC+ (carrying +15% of body weight in a vest) in a 3 ( n = 32) or 6 ( n = 21) week intervention (3 sessions/week). Data was analysed by mixed models approach. Rate of perceived exertion (RPE; Borg scale 6-20; mean values from 3 and 6 weeks) during training did not differ between CON (12.3 ± 0.4), ECC (11.5 ± 0.3), and ECC+ (11.7 ± 0.4). After 6 weeks, leg muscle mass increased more in ECC+ (+0.29 ± 0.09 kg) vs CON (+0.08 ± 0.05 kg) ( P <0.05) but not different from ECC (+0.16 ± 0.06 kg). 6-minute walk test (6MWT) increased after 6 weeks more ( P <0.05) in ECC+ (+85 ± 23 m) compared with ECC (+37 ± 13 m) and CON (+27 ± 12 m). Intramyocellular glycogen content increased from 359 ± 19 nmol/mg d.w. in CON (to 511 ± 65 and 471 ± 44 after 3 and 6 wks, respectfully ( P <0.05)), but not in ECC (to 344 ± 28 after 6 weeks) or in ECC+ (to 389 ± 20 after 6 weeks). Conclusion: carrying extra weight while descending stair walking do not increase RPE, but the ECC+ training resulted in greater muscle responses compared with CON, but glycogen synthesis was stimulated only in CON. Descending stairs is a simple model for prevention and treatment of sarcopenia and the stimulus is enhanced by carrying extra weights.